Sumbangan Ulamak berketurunan Jawa di Selangor dalam Perkembangan Islam Sebelum Merdeka: The contributions of Javanese scholars (Ulamak) in Selangor towards Islamic Expansion before Independence - Ab Rahim, Aisyah; Mohd Nor, Mohd Roslan (Online Journal of Research in Islamic Studies, 2020)
This article studies the contribution of two scholars or ulamak in Selangor before the independence of Malaya. The two ulamak are Kiyai Muhammad Ali Qaribun and Kiyai Khalil Ibn Abu Ammar. Both ulamak are of Javanese descent who settled in Selangor and have made many contributions not only in Islamic preaching but also in various fields such as establishing the pondok educational institutions, serving the community as teachers, imams, kadis and producing books that has influenced and changed the socio-economic, educational, social and cultural backgrounds of Selangor. The objective of this study is to highlight the ulamak in Selangor as reference to the community and acknowledge their contributions to Selangor.